Características biométricas, trocas gasosas e atividade do sistema antioxidante de plantas de eucalipto durante o cres- cimento inicial - Delias, Dominique dos Santos (2013)
Eucalyptus is a genus with origin in Australia and has expanding in several regions of Brazil, mainly due to its wide aclimatation. But there are certain regions with climatic characteristics that may limit the growth and development of eucalyptus plants, resulting in abiotic stress. In this context, monitoring the inicial growth of plants allows us a better understanding about species that survive better against the heterogeneous environment, enabling the good quality seedlings production. This work aimed to analyze the behavior of biometric characteristics, gas exchange and the antioxidant system activity of plants of two species of Eucalyptus, E. grandis and E. saligna during inicial growth. Samples were collected monthly between 2011 July and 2012 July. On 2011 May, nursery seedlings were transplanted to 5 L plastic bags, containing a mixture of soil and sand (2:1). We evaluated biometric characteristics (stem diameter at 10 cm from the soil, diameter at half height of the plant stem, plant height, leaf number, leaf area and dry weight of leaf, stem, root and total dry weight), biochemical characteristics (activity of Superoxide Dismutase, Catalase and Ascorbate Peroxidase enzymes, quantification of hydrogen peroxide and lipid peroxidation) and gas exchange (rate of CO2 assimilation, intracellular concentration of CO2, stomatal conductance and transpiration). The results showed that E. saligna had higher growth than E. grandis. Regarding biochemical analyzes, E. grandis had higher activity of antioxidant enzymes at the beginning and end of the experiment, that represents the cold seasons. E. saligna showed increased activity only in the second season of cold. For gas exchange differences occurred between species and between the evaluations times. In general, it was found that plants E. grandis and E. saligna showed similar responses face of climatic conditions of the region studied, and this research confirms their initial growth adaptability to climatic conditions of Rio Grande do Sul State.